2021
DOI: 10.1155/2021/6661588
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Antibiotics for Urinary Tract Infections after Urodynamic Studies: A Meta‐Analysis

Abstract: Aim. We aimed to perform a meta-analysis to determine whether antibiotic prophylaxis reduces the incidence of urinary tract infections (UTIs) after urodynamic studies (UDS). Methods. We conducted a systematic search of PubMed, Web of Science, Ovid, Elsevier, ClinicalKey, Embase, Cochrane Library, Medline, and Wiley Online Library. Randomized controlled trials (RCTs) comparing the effectiveness of prophylactic antibiotics with placebo or no treatment in preventing UTI after UDS were included. Two reviewers extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Meanwhile, the incidence of GUTI after UDS was 4.2% and 4.7%, respectively, and the GUTI‐free rate within 7 days after UDS was found the equivalence. A meta‐analysis 5 of the efficacy of AP on GUTI (or UTI) after UDS showed that there was a significant difference between with and without AP. On the other hand, there are several studies 2 , 3 , 17 that show no significant differences of the frequency of subsequent UTI development between with and without AP, but the equivalence of incidence has not been verified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the incidence of GUTI after UDS was 4.2% and 4.7%, respectively, and the GUTI‐free rate within 7 days after UDS was found the equivalence. A meta‐analysis 5 of the efficacy of AP on GUTI (or UTI) after UDS showed that there was a significant difference between with and without AP. On the other hand, there are several studies 2 , 3 , 17 that show no significant differences of the frequency of subsequent UTI development between with and without AP, but the equivalence of incidence has not been verified.…”
Section: Discussionmentioning
confidence: 99%
“…For the sample size, our previous data 13 showed that the GUTI‐free rate within 7 days after UDS was about 96%, and if we assume that this rate does not change before and after the appearance of COVID‐19, the sample size that satisfies a 80% detection power with an alpha error of 5% would be about 168 cases in each group with 1:1 allocation, for a total of 336 cases, and we designed the patient population to meet this requirement. The equivalence margin was set at 6%, which is corresponding to a half of the lower limit of the confidence interval, based on the results of the meta‐analysis 5 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most societies recommend against treating it, as many studies have not found any benefit from antibiotics [ 119 ]. Nevertheless, a recent meta-analysis found a higher rate of symptomatic UTI in patients with previous AB who did not receive antibiotic prophylaxis (RR = 0.65, 95% CI: 0.48–0.88) [ 120 ]. However, they did not analyse more severe complications (sepsis, hospitalization, and death).…”
Section: Asymptomatic Bacteriuriamentioning
confidence: 99%
“…Although risk factors for UTI after UDS were identified in the latter 2 studies, both authors report low incidence of UTI after UDS and recommend against antibiotic prophylaxis. In 2021, Wu et al 8 also performed a meta-analysis, which included studies in both male and female patients in which the authors concluded that the use of antibiotic prophylaxis reduced the incidence of both bacteriuria and UTI after UDS. This is in contrast to the UDS guidelines, which recommend against antibiotic prophylaxis except for high-risk patients.…”
mentioning
confidence: 99%